2020
DOI: 10.1039/c9dt04560k
|View full text |Cite
|
Sign up to set email alerts
|

Addition reactions and diazomethane capture by the intramolecular P–O–B FLP: tBu2POBcat

Abstract: FLPs, R2POBcat (R = tBu 1, Mes 2), are shown to react with a variety of substrates including diazomethanes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
48
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 29 publications
(50 citation statements)
references
References 64 publications
2
48
0
Order By: Relevance
“…Zhu et al 42 have reported the formation of several heterocycles by addition reactions of POB based intramolecular FLPs (R2POBcat) with small molecules like PhOH, CO2, CS2, PhNCO, MesCNO, O2, 9,10-phenanthrenedione, and diazomethanes.…”
Section: Silylation and Borylation By Flpsmentioning
confidence: 99%
“…Zhu et al 42 have reported the formation of several heterocycles by addition reactions of POB based intramolecular FLPs (R2POBcat) with small molecules like PhOH, CO2, CS2, PhNCO, MesCNO, O2, 9,10-phenanthrenedione, and diazomethanes.…”
Section: Silylation and Borylation By Flpsmentioning
confidence: 99%
“…Over the years, a wide library of ambiphilic compounds has been developed, in particular with phosphines as Lewis basic sites. A number of spacers varying in size and rigidity have been investigated, and P^E compounds of type I – IV (E = B, Al, Si, Sn…‐based Lewis acids) featuring a one‐atom spacer (^ = C, N, O) are an important subclass of ambiphilic derivatives (Figure ) …”
Section: Figurementioning
confidence: 99%
“…[5a] Later on, Ia was shown by Zargarian and Fontaine to display ambiphilic behavior upon coordination to transition metals. Since 2006, increasing interest has been devoted to such P^E compounds, in particular to C(sp 2 )‐bridged derivatives of type II , and most recently, to O‐bridged species of type IV …”
Section: Figurementioning
confidence: 99%
See 2 more Smart Citations